Application Of Activated Candlenut Shell Using Potassium Hydroxide For Iron Reduction (Fe TO FeSO4) - Wara Dyah Pita Rengga; Maharani Rani; Ashar Shidqi (Universitas Muslim Indonesia, 2019)
This study aims to prepare carbon from candlenut shell by carbonation and activation of 1M KOH which is used to adsorb Fe 2+ in solution. The activation process produces changes in structure and functional groups on activated carbon. This study studied the effect of carbonation temperatures of 800 o C with the concentration of activator is KOH 1M with 24 hours activation time. The initial concentration of the solution affects the adsorption capacity of activated carbon, the greater the initial concentration of the solution which is at 5 mg/L, the greater the adsorption capacity. Optimum adsorption occurs at pH 7 by providing an increase of Fe 2+ absorption of ± 7 mg/g and contact time is 120 minutes. The equilibrium review is used using the Langmuir and Freundlich isotherm models , where the most suitable equilibrium is the Freundlich Isotherm model with a value of R 2 = 0.9 848 ; K F = 4,427 ; n = 3,475 . It can be concluded that the activated carbon from the candlenut shell is able to absorb Fe 2+ metal in FeSO 4 solution.